Adobe InDesign CC 2014 release learn by video - Chelius, Chad (Peachpit Press, 2014)
"This critically-acclaimed interactive training program from Adobe Press offers exceptional quality high-definition video to teach the fundamentals of Adobe Indesign CC (2014 release). Including more than 9 hours of video tutorials, the course comes complete with lesson files, assessment quizzes, and review materials. Experienced instructor Chad Chelius presents a comprehensive introduction to InDesign, including best practices as well as fundamental layout and document styling concepts. Topics covered include working with text, styles, and objects, and outputting files as ePubs, and how to work within the Creative Cloud."--Resource description page.
Title from title screen (viewed Aug. 20, 2014)
Keywords: Adobe InDesign (Electronic resource); Desktop publishing; Éditique; desktop publishing